Burundi : Poverty Reduction Strategy Paper-Progress Report. (IMF Staff Country Reports; Country Report ;, 2011)
The government of Burundi undertook to prepare the first Growth and Poverty Reduction Strategy Framework (GPRSF). The general framework for most economic and social development programs initiated by Burundi and its donors has been established. A general balance sheet of performance has also been established. Economic development efforts have generally had an impact on the population's material well-being. The principal objective of the second strategic axis focusing on economic growth was annual growth between 6 and 7 percent, capable of doubling per capita GDP in 15 years.